Overexpression of CtCHS1 Increases Accumulation of Quinochalcone in Safflower - Dandan Guo; Yingru Xue; Dongqiao Li; Beixuan He; Xinlei Jia; Xin Dong; Meili Guo (Frontiers in Plant Science, 2017)
Carthami flos, the dried petal of safflower (Carthamus tinctorius L.) has been widely used in traditional Chinese medicine to treat cardiovascular and cerebrovascular diseases, in which quinochalcone glucosides such as hydrosafflower yellow A (HSYA), carthamin are uniquely present and have been identified as active compounds. In the present study, through sequencing of a safflower floret cDNA library and subsequent microarray analysis, we found 23 unigenes (5 PALs, 1 C4Hs, 5 4CLs, 6 CHSs, 2 CHIs, 2 DFRs, 2 FLSs) involved in flavonoid pathway, of which 4 were up-regulated differentially during quinochalcone glucosides accumulation with the floret developing stage. The up-regulated genes were verified by PCR methods. Considering chalcone synthase are entry enzyme in flavonoid biosynthesis, CHS1 was focused on target gene to verify its function furtherly. Bioinformation analysis showed that CHS1 shared 86.94% conserved residues with CHS from other plants. Subcellular localization showed that CtCHS1 was localized in cytoplasm in onion epidermal cells. The transgenic safflower plant with overexpression CtCHS1 by Agrobacterium-mediated pollen-tube pathway method was firstly generated. The results present that expression of PAL2, PAL3, CHS1, CHS4, CHS6 increased and expression of CHI1 and CHI2 decreased in the transgenic plant floret. Meanwhile, the accumulation of quinochalcone glucosides increased by ∼20–30% and accumulation of quercetin-3-β-D-glucoside and quercetin decreased by 48 and 63% in the transgenic plant floret. These results suggested that CtCHS1 played an important role in quinochalcone glucosides biosynthesis rather than flavonol biosynthesis. These results also demonstrated that the pollen-tube pathway method was an efficient method for gene transformation in safflower. Our study will provide a deep understanding of potential synthetic genes involved in quinochalcone biosynthetic pathway.